Code-Switching in Agus Sanetyo’s Business Motivational Talk Video: The Hidden Cuan in Your Business - Ivon Christy Hiandaka (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
The writer conducted this study to analyze the types and functions of code-switching used by Agus Sanetyo in a business motivational talk video entitled The Hidden Cuan in Your Business. In conducting the study, the writer uses the theory of the types of code-switching by Poplack (1980) and the theory of the functions of code-switching by Appel and Muysken (2005). This research was done using a qualitative descriptive approach. The writer found out that in this study, Agus Sanetyo used all three types of code-switching types and three of six functions of code-switching, with the most used type was the intra-sentential and the most function used was the referential function. In conclusion, analyzing the types and functions of code-switching could bring us to understand the hidden motivations behind it.Keywords: bilingual, code-switching, business-setting, intra-sentential, referential function